Pkd1 and Wnt5a genetically interact to control lymphatic vascular morphogenesis in mice. Issue 2 (16th July 2021) - Chau, Tevin C. Y.; Baek, Sungmin; Coxam, Baptiste; Skoczylas, Renae; Rondon‐Galeano, Maria; Bower, Neil I.; Wainwright, Elanor N.; Stacker, Steven A.; Cooper, Helen M.; Koopman, Peter A.; Lagendijk, Anne K.; Harvey, Natasha L.; et al.
ABSTRACT: Background: Lymphatic vascular development is regulated by well‐characterized signaling and transcriptional pathways. These pathways regulate lymphatic endothelial cell (LEC) migration, motility, polarity, and morphogenesis. Canonical and non‐canonical WNT signaling pathways are known to control LEC polarity and development of lymphatic vessels and valves. PKD1, encoding Polycystin‐1, is the most commonly mutated gene in polycystic kidney disease but has also been shown to be essential in lymphatic vascular morphogenesis. The mechanism by which Pkd1 acts during lymphangiogenesis remains unclear. Results: Here we find that loss of non‐canonical WNT signaling components Wnt5a and Ryk phenocopy lymphatic defects seen in Pkd1 knockout mice. To investigate genetic interaction, we generated Pkd1 ; Wnt5a double knockout mice. Loss of Wnt5a suppressed phenotypes seen in the lymphatic vasculature of Pkd1 −/− mice and Pkd1 deletion suppressed phenotypes observed in Wnt5a −/− mice. Thus, we report mutually suppressive roles for Pkd1 and Wnt5a, with developing lymphatic networks restored to a more wild type state in double mutant mice. This genetic interaction between Pkd1 and the non‐canonical WNT signaling pathway ultimately controls LEC polarity and the morphogenesis of developing vessel networks. Conclusion: Our work suggests that Pkd1 acts at least in part by regulating non‐canonical WNT signaling during the formation of lymphatic vascular networks. Key Findings: Pkd1 vascular knockout leads to loss of polarity in mesenteric lymphatic valves. Wnt5a knockout lymphatics show similar polarity defects as previously reported for Pkd1 mice. Knockout of the non‐canonical Wnt co‐receptor Ryk shows vessel morphogenesis defects similar to Pkd1 knockout mice. Double Wnt5a, Pkd1 knockout mice reveal a surprising genetic interaction between the two genes.